Heaven’s bankers: inside the hidden world of Islamic finance, by Harris Irfan, The Overlook Press, 2015, xx + 347 pp., ISBN 978-1-4683-1047-4 - Ariffin, Muhammad Irwan (2016)
Islamic finance started to get the world’s attention as it collides with capitalist interest of profit maximization at the global level. During this time, Harris Irfan was among the early generation of ‘structurers’ who were responsible in designing financial contracts that are appealing to the conventional investors and observe Shariah requirements. Despite having an illustrious beginning, Irfan’s journey into the world of Islamic finance has eventually sparked a puzzle within himself: Is Islamic finance heading towards the right direction? He started to critically evaluate Islamic financial industry by focusing on the legal and moral aspects of Islamic finance based on both the letter and spirit of Islamic law. Irfan managed to share his rich professional experience and personal acquaintance with scholars to expose the false flag of Islamic finance and how it is lurking the harms which it seeks to avoid in the first place.